British Attitude towards American expansion in Caribbean (Journal of the College of Education for Women, 2019)
This paper deals with the nations of British American Struggle in Caribbean. Itexplains British Navy attitude of American expansion in Caribbean. Then continuation ofAmerican expansion in the same place and Britain failure to limit it. This paper high lights thebeginning of acceptance between Britain's and United state, especially after Britishsubmission to United States in Caribbean. Then we study the Anglo – American harmony andthe affection on the Anglo – American relation.This paper concludes that American influences in Americans which is a truth.